Group Counseling with Symbolic Modeling Technique to Improve Students Career Decision Making Self-Efficacy - Sadewi, Aulia Ika; Wibowo, Mungin Eddy; Sugiyo, Sugiyo (Jurnal Bimbingan Konseling, 2019)
Self-efficacy focuses on the component of self-confidence that a person has in doing his tasks including career decision making. To be able to decide the career appropriately, students need confidence in making choices based on their abilities. This study aimed to improve self-efficacy in students’ career decision making through group counseling with symbolic modeling technique. The experimental research method with one group pre-test post-test design was used and involved eight students as group members. After their data were analyzed by using the Wilcoxon test, it showed that group counseling with symbolic modeling technique was effective to improve self-efficacy in students’ career decision making. Further, the discussion of this study is directed at identifying the implication of group counseling with symbolic modeling technique to improve self-efficacy in students’ career decision making.